CRITICAL INTERCULTURALITY AS AN EDUCATIONAL PROCESS EXPERIENCES IN AN INDIGENOUS COMMUNITY IN NORTHWEST MEXICO - González-Machado, Emilia Cristina; Santillán-Anguiano, Ernesto Israel (SocioEdu: Sociological Education, 2024)
This article is the result of a pedagogical project in the community of Santa Catarina, in northwestern Mexico. First, we analyze the theoretical implications of interculturality, in particular the concept of critical interculturality. In Latin America, critical interculturality has contributed to decolonial studies, creating a framework for understanding social relations within the framework of Modernity. We epistemically assume that critical interculturality emerges and is nourished by social movements. Critical interculturality is thus defined as an ongoing political project. Secondly, we present the Pa Ipai community of Santa Catarina, describing its historical and social conditions. We assume that as socio-educational researchers we must permanently question our methodology to avoid academic colonialism. Unfortunately, however, this is often reproduced when we consider community members as mere informants. Finally, we outline an overview of the objectives and procedures of the critical intercultural pedagogical project, followed by some reflections on the difficulties and results of said project. This proposal aims to understand interculturality as a process, a work in progress, where other forms of knowledge come into play. By creating a space away from traditional school environments, the backbone of the learning process is to involve students with a plurality of cultural manifestations that bring them closer to an ontological understanding of the other.